Density–Porosity Interplay in Epoxy‑Based Syntactic Foams Reinforced with K15 Glass‑Silica Microballoons - Hidyus, Sofi Alifia; Budiwirawan, Agung; Musyono, Ari Dwi Nur Indriawan; Setiadi, Rizky; Bunyamin, Bunyamin (Sainteknol : Jurnal Sains dan Teknologi, 2025)
Syntactic foam is a lightweight, high‑strength composite consisting of a polymer matrix filled with hollow microspheres (microballoons). This study examines how the volume fraction of glass‑clad silica microballoons K15 (10–50 vol %) affects the density, porosity, and void distribution of epoxy‑bonded syntactic foams. Specimens were molded in accordance with ASTM D790, conditioned for 48 h (23 ± 2 °C; 50  ±  5 % RH), and their density was measured by the pycnometric method specified in ASTM D792. Porosity was calculated theoretically and validated by SEM–EDS imaging of fracture cross‑sections. Results show a linear decrease in density from 1.15 g cm⁻³ (0 vol %) to 0.63 g cm⁻³ (50 vol %), while porosity rises exponentially from 2.7 % to 18.4 %. Morphological analysis confirms a homogeneous microballoon dispersion up to 30 vol %, but agglomeration and interbinder voids appear above 40 vol %, leading to uncontrolled porosity. A strong negative correlation (R² = 0.96) is observed between density and effective porosity. A 30 vol % K15 loading is identified as the optimum, achieving a 28 % density reduction without a significant porosity spike. These findings provide a basis for designing sandwich cores and amphibious flotation structures that require high strength‑to‑weight ratios.